Distance Education Management via Satellite of Teachers in Small-sized School Under Pathumthani Primary Educational Service Area Office 2: Distance Education Management via Satellite of Teachers in Small-sized School Under Pathumthani Primary Educational Service Area Office 2 - Sangchan, Wanida; Phetsatit, Pongsak; Sirivisitkul, Sanit (RATANABUTH JOURNAL, 2024)
For developing countries, standardizing education was important. Distance education via satellite was important solution to create standards and equality in education provision. This objective of this research was to study the conditions and compare the differences in distance education management via satellite of teacher in small-sized school under Pathumthani primary educational service area office 2, categorized by personal factors. The sample consisted of 90 teachers from small-sized school in Pathumthani primary educational service area office 2. The research instrument used was a questionnaire. The statistical methods employed included frequency, percentage, mean, standard deviation, t-test, and F-test. The findings revealed that, overall, distance education management via satellite of teacher in small-sized school under Pathumthani primary educational service area office 2 was at a high level. When broken down into specific aspects, the highest mean score was in the context of satellite-based distance education management, while the lowest mean score was in the process of satellite-based distance education management. The hypothesis testing indicated that differences in personal factors did not significantly affect teachers’ opinions on distance education management via satellite of teacher in small-sized school under Pathumthani primary educational service area office 2.